3'UTR Polymorphism of NRAMP1 Gene and Susceptibility to Lung Tuberculosis among Patients and Nurses in Surabaya, Indonesia - Anggraini, Rahayu (Institute of Topical Disease Universitas Airlangga, 2010)
The objectives of this study was to evaluate a potential role for natural-resistance-associated macrophage protein 1 (NRAMP1) gene in the human homologue using four single base pair polymorphisms (D543N, 3'UTR, INT4, 274C/T) for susceptibility to tuberculosis infection in Surabaya, Indonesia. The study population were 69 lung tuberculosis patients and 43 healthy nurses were genotyped with the polymerase chain reaction (PCR) and the product amplified from their genomic DNA were subjected to restriction enzyme digestion (RFLP) and were analysed using agarose gel electrophoresis. Results of this study showed only the homozygous TGTG deletion allele at the 3'untranslated region (3'UTR) of the NRAMP1 gene i.e. the TGTGdel/del genotype was more frequently found in lung tuberculosis patients (20/69=29%) compared to that found in nurses (2/43=4.7%). The Odds ratios (ORs) were 8.37 (95% confidence interval [CI], 1.85 to 37.94; p=0.002). This finding shows that polymorphism 3'UTR of NRAMP1 gene increased the risk of lung tuberculosis in Surabaya, Indonesia.